Influence of permafrost microorganisms on morphophysiological indicators of spring wheat - A. M. Subbotin; M. V. Narushko; N. A. Bome; S. A. Petrov; V. A. Malchevskiy; M. A. Gabdullin (Вавиловский журнал генетики и селекции)
Biologically active compounds on the basis of highly efficient strains of bacteria of the genus Bacillus are currently being sought for to increase the yield of grain crops in the North. There is a number of biological products available, including those based on bacteria in the genus Bacillus (Phytosporin-M, Bactofit, Gamair, Integral, and other). However, the effectiveness of these drugs in the northern regions may be reduced, because the activity of introduced microorganisms depends on their adaptability in the rhizosphere and rhizoplane. This article describes the effect of bacteria of the genus Bacillus in permafrost on the morphological and physiological indicators of seedlings of soft spring wheat variety Irgina. These indicators are germination energy, laboratory seed germination, length and wet weight of roots and shoots of seedlings, as well as the length of coleoptile and number of chlorophylls a, b and carotenoid in the pigment extract from the plant material. It has been demonstrated that germination and morphometric parameters were significantly higher following exposure to Bacillus strains in permafrost than following treatment with the current strain of Phytosporin-M. It is likely that in the process of swelling of seeds (during their preplant treatment) Bacillus bacteria reach the caryopsis with water and begin to cleave spare nutrients actively, making them easier accessible for assimilation by seedlings. It is proposed that the increase in morphophysiological indicators of spring wheat variety Irgina is also a consequence of stimulation of the photosynthesis system and, consequently, an increased efficiency of absorption of light energy. Considering how differently different strains of bacteria isolated from permafrost influence the morphological and physiological and biochemical parameters of the plant, it appears that these strains or their combinations can be used for the development of biologics ensuring a comprehensive effect.